Outcome Metrics in the Treatment of Carpal Tunnel Syndrome: A Systematic Review. (July 2022) - Mertz, Kevin; Lindsay, Sarah E.; Morris, Arden; Kamal, Robin N.
Background: The purpose of this systematic review was to determine the metrics used to assess outcomes after treatment for carpal tunnel syndrome. Methods: We performed a systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines of level I and II randomized controlled trials of treatment for carpal tunnel syndrome. We searched the PubMed/MEDLINE electronic database for studies on treatment of carpal tunnel syndrome from January 2008 to January 2018. A total of 105 studies were included in the final analysis. The metrics used to assess outcomes in each studies were collected, compared, and described. Results: Nearly all the studies used a patient-reported outcome measure (PROM) to assess outcomes (94%). The most common PROMs used were the Boston Carpal Tunnel Questionnaire (60%) and the Visual Analog Scale for pain (51%). Electrophysiological testing and physical examination were also commonly used to assess outcomes (50% and 46%, respectively). Cost, sleep, and return to activities of daily living were assessed in a minority of studies (1%, 1%, and 5%, respectively). Conclusions: Successful treatment of carpal tunnel syndrome is commonly defined based on a PROM, highlighting recent efforts to measure outcomes from the patient's perspective. Other patient-centered metrics such as return to work and sleep quality, however, were rarely reported, whereas objective measures such as nerve conduction studies were prevalent. Further work is needed to determine patients' preferred method of measuring outcomes after treatment for carpal tunnel syndrome to inform goal-directed decision-making and treatment.